VIRTUAL REALITY ART INSTALLATIONS POWERED BY AI - Singh, Poonam; Raj, Nimesh; Bhosale, Varsha Kiran; Gupta, Shikhar; Trivedi, Nishant; Panigra, Abhijeet (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This paper looks at the intersection between Artificial Intelligence (AI) and Virtual Reality (VR) and the way it is shaping the next generation of digital artworks. With the ease of expression created by technology, AI-assisted VR environments are altering the process of creation, the ownership of the piece, and how it reaches the masses. The paper will analyse how the virtual art has been developed over the course of years, starting with the initial digital art, to the most recent visual and interactive art driven by AI. The development of machine learning and creative algorithms allows computers to construct pictures independently, and the work of neural networks allows the appearance of the things in virtual locations to be altered in real time. Natural Language Processing (NLP): It is also employed in order to make the stories interactive. This will enable the users to co-create and modify the art experience through conversation and mood tracking. The paper also ventures into technical details of the manner in which such kinds of systems are developed and assembled, the hardware, software structure and model fusion methodologies. Besides discussing the scientific aspect of it, it discusses the effects of creativity and culture, poses the question of what is the evolving role of the artist, as well as the social issues of AI-generated creation. All these are authorship, computer bias, and cultural portrayal that are critically discussed. The other social and cultural consequences of interactive art using AI include consideration of the accessibility, emotional appeal and social engagement of the kind of art.